Effects on bleeding complications of pharmacogenetic testing for initial dosing of vitamin K antagonists: a systematic review and meta‐analysis. (24th July 2014) - Franchini, M.; Mengoli, C.; Cruciani, M.; Bonfanti, C.; Mannucci, P. M.
Summary Background Although warfarin and other vitamin K antagonists (VKAs) are the most widely used oral anticoagulants for the prevention and treatment of thromboembolic events, a number of factors hamper their manageability, the most important being the inter‐individual variability of the therapeutic dose requirement. Following the discovery of the influence of CYP2C9 and VKORC1 polymorphisms on VKA dose requirements, there has been interest in genotype‐guided VKA dosing in order to reduce the risk of over‐anticoagulation at the time of therapy initiation and hence the risk of bleeding, particularly prominent during the early days of treatment. To assess the impact on clinical outcomes of pharmacogenetic testing for initial VKA dosing, we have performed a systematic review and meta‐analysis of the literature. Methods MEDLINE, EMBASE and Cochrane databases were searched up to March 2014. Only randomized controlled trials comparing genotype‐guided vs. clinically‐guided warfarin dosing were included. Results Nine trials including 2812 patients met the inclusion criteria and were pooled for meta‐analytical evaluation. Risk of bias, assessed according to the Cochrane methodology, showed a low risk for the majority of domains analyzed in the included trials. A statistically significant reduction in the risk ratio (RR) for developing major bleeding events was observed in the pharmacogenetic‐guided group compared with the control group (RR = 0.47; 95% CI, 0.23–0.96; P = 0.040). Conclusions The results of this meta‐analysis show that genotype‐guided initial VKA dosing is able to reduce serious bleeding events by approximately 50% compared with clinically‐guided dosing approaches.